Inequality regimes in male-dominated trades: What role do apprenticeship intermediaries (GTOs) play?. (September 2022) - Bamberry, Larissa; Bridges, Donna; Wulff, Elizabeth; Krivokapic-Skoko, Branka
In Australia and internationally, women continue to be underrepresented in male-dominated trade occupations. A notable barrier is the apprenticeship system, which requires women to overcome obstacles in employment and training. Government and industry stakeholders have encouraged women's apprenticeships in male-dominated trades through the development of Group Training Organisations' (GTOs) that operate as intermediaries between apprentices and employers. Extending Acker's model of workplace inequality regimes, we argue that inequality regimes operate between organisations at an industry-wide level. We ask ' Do GTOs operate to produce and reproduce workplace and industry-wide inequality regimes? Or can they facilitate improved gender diversity in male-dominated trades? ' Drawing on a recent study of regional tradeswomen's employment, we find that although GTOs have an important role in facilitating gender diversity, they have inconsistent results in challenging existing inequality regimes. There is a risk that they may become a vector of transmission for workplace inequality regimes to the broader industry. JEL Codes: R23, J71, I24